Hadis dan Mitos Jawa (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2017)
Tulisan ini dibuat dengan maksud untuk mengkaji kebenaran dari mitos-mitos yang dimunculkan oleh orang jawa. Mitos memiliki kaitan yang sangat erat dengan budaya masyarakat jawa karena budaya jawa selalu mengangkat mitos dalam ritual-ritual yang dilaksanakan. Di sisi lain ada hadis yang selaras dengan beberapa yang dipercayai oleh orang jawa. Mitos wewe gombel dan rizki yang dipatuk ayam menjadi obyek yang menarik untuk dikaji, dengan harapan ditemukannya kaharmonisan antara hadis Nabi dengan mitos-mitos jawa. Pada akhirnya, mitos jawa tidak selalunnya harmonis dengan Hadis Nabi SAW.This paper was created with the intention to examine the truth of the myths raised by the Javanese. Myths have a very close relationship with Javanese culture because Javanese culture always lift the myth in the rituals that are implemented. On the other hand there are hadiths that are in harmony with some Javanese beliefs. Myths wewe gombel and rizki pecked chicken is one example of the myth of Javanese society who have sides of philosophical teachings and interesting to be studied. Actually there is harmony between the hadith with the targeted meaning of myth. But that needs to be underlined is the myth of Java is not always harmonious with the Hadith of the Prophet SAW